IgY Technology in aquaculture – a review. (20th February 2014) - Baloch, Abdul Rasheed; Zhang, Xiao‐Ying; Schade, Rüdiger
Abstract Since the discovery of IgY in egg yolk in late 1800s, many applications of this antibody in diagnostics and therapeutics have been reported in human and veterinary medicine. The mass use of antimicrobial agents in aquaculture has caused the resistance in certain bacteria, and these fish pathogens cause tremendous economic losses in aquaculture industry coupled with antibiotic resistance, consequently causing barriers in international trades. IgY antibodies have been developed for the treatment and prevention of certain fish diseases such as white spot syndrome in shrimp, vibriosis, enteric redmouth disease and edwardsiellosis. These antibodies are also developed for the recognition of developing and mature stages of Loma salmonae (microsporidia) in the farmed pacific salmon. Other uses of IgY in aquaculture include the development of sandwich ELISA for the detection of ciguatoxin (a poisonous organic compound) in the tissues of fish, and recently, potential sea food persevering properties of IgY have been revealed. Our review presents an analysis of the characteristics, extraction methods, therapeutic, detection, and seafood‐persevering applications of IgY antibodies in aquaculture.